Decision Support System Using Cloud-Based Moka Pos Application To Easy In Input In Orange Carwash Blulukan Flash N0.110 Colomadu - Ayu Sri Muryani; Muqorobin Muqorobin (Institut Teknologi Bisnis AAS Indonesia, 2020)
Orange Carwash is a car wash service business that has been running in 2018, Orange Car. The wash address that I studied is located at Jalan Adi Sucipto no.110 Blulukan Colomadu In running a car wash service business, Orange Carwash tries to provide services to customers, regarding inputting types of washing products, member entry, express washing promos, and payment transaction methods. The system used is still classified as manual. For the purpose of this research, it really helps companies in terms of promoting and introducing products to car wash consumers with a computerized system using the cloud-based Moka Pos application. The method in this research is through observation, interviews, documentation, and heritage studies (looking for references from books or journals). The system design is made with context diagrams, HIPO, DAD, input output design, hardware requirements analysis, software requirements analysis. By using online input, the cashier will find it easier to group the washing type product data, as well as compile accurate and efficient reports. The final result of designing an online car wash service information system, using the Moka Pos application, in the form of sales report recap data and the number of types of washing products, classification of types of washing products, and the washer name of each cashier, which will be designed by the car wash. Oranger Carwash.